Complete sequence and variability of a new subgroup B nepovirus infecting potato in central Peru - Souza, Joao de; Muller, G.; Pérez, W.; Cuéllar, Wilmer Jose; Kreuze, Jan F. (Springer, 2017)
The complete bipartite genome (RNA1 and RNA2) of a new nepovirus infecting potato was obtained using small RNA sequencing and assembly complemented by Sanger sequencing. Each RNA encodes a single polyprotein, flanked by 5’ and 3’ untranslate regions (UTR) and followed by a poly (A) tail. The putative polyproteins encoded by RNA1 and RNA2 had sets of motifs which are characteristic of viruses in the genus Nepovirus. Sequence comparisons using the Pro-Pol region and the coat protein, including phylogenetic analysis of these regions, showed closest relationships with nepoviruses. The data obtained support the taxonomical status of this new virus (putative named Potato virus B, PVB) as a member of the genus Nepovirus, subgroup B.